Lentiviral CRISPRa/i in the adult prairie vole brain: modulating neuronal gene expression without DNA cleavage - Loth, Meredith K.; Mesch, Kendall T.; Herrera-Garcia, Celine; Brusman, Liza E.; Donaldson, Zoe R. (Frontiers in Genome Editing, 2025)
Prairie voles (Microtus ochrogaster) are a powerful model for studying the neurobiology of social bonding, yet tools for region- and cell type-specific gene regulation remain underdeveloped in this species. Here, we present a lentivirus-mediated CRISPR activation and interference (CRISPRa/i) platform for somatic gene modulation in the prairie vole brain. This system enables non-mutagenic, titratable regulation of gene expression in the adult brain without germline modification. Our dual-vector system includes one construct expressing dCas9-VPR (VP64-p65-Rta) referred to as CRISPRa or dCas9-KRAB-MeCP2 (Kruppel-associated box-methyl CpG binding protein 2), referred to as CRISPRi under a neuron-specific promoter, and a second construct delivering a U6-driven sgRNA (single guide RNA) alongside an elongation factor 1 alpha (EF1α)-driven mCherry reporter. We detail the design, production, and stereotaxic delivery of these tools and demonstrate their application by targeting four genes implicated in social behavior (Oxtr, Avpr1a, Drd1, and Drd2) across two mesolimbic brain regions: the nucleus accumbens and ventral pallidum. Gene expression analyses confirmed robust, bidirectional transcriptional modulation for selected targets, establishing a proof of concept for CRISPRa/i in this non-traditional model. The dual-vector design is readily adaptable to other gene targets, cell types, and brain regions, and can be multiplexed to provide a flexible and scalable framework for investigating gene function in behaviorally relevant circuits. These advances represent the first successful implementation of somatic CRISPRa/i in prairie voles and expand the genetic toolkit available for this species.